Risk takers: PDS partners developing and sustaining antifragile teachers - Lianne Jones; Rachelle Rogers; Doug Rogers; Austin McClinton; Lisa Painter (Emerald Publishing, 2023)
Purpose - The ever-changing educational landscape, exacerbated by recent events surrounding COVID, political and cultural unrest, necessitates educators who are antifragile, able to withstand pressures and thrive amidst uncertainty. To this end, the pilot study reported here aims to examine mathematics educators' initial reflections on what it means to be a risk-taker in the classroom, what prevents them from engaging in instructional risks and what would support their instructional risk-taking. Design/methodology/approach - The pilot study utilized interviews with participants, including four pre-service teachers who were enrolled at the university and seven in-service teachers who were employed on active PDS campuses within the school district. Findings - Preliminary findings suggest teacher beliefs concerning risk-taking, the barriers to engaging in such behaviors and the support needed to be able to take instructional risks. Results highlight the role of school-university partnerships in cultivating a culture of risk-taking through active collaboration and dialogue. Research limitations/implications - These findings have important implications for universities and PDS partners engaged in preparing teachers for an educational field that is unpredictable and continually changing. Additional research should be completed in varying PDS settings. Practical implications - Findings highlight the role of school-university partnerships in cultivating a culture of risk-taking through active collaboration and dialogue. Originality/value - Educators are currently faced with an unprecedented instructional landscape. Antifragile, risk-taking teachers are needed who are adaptable and innovative, thus better equipped to enter the challenging and uncertain realities of education.